The Assessment of the Clubfoot Children’s Orthotic need for the development of the Foot Abduction Orthosis (FAO) prototype design - Sani, Mohd Najib Abdullah; Kamil, Muhammad Jameel Mohamed; Azahari, Baharin; Sulaiman, Abdul Razak (World Research Library, 2018)
Foot abduction is an imminent component of treatment within the Ponseti method. It is a treatment procedure where the clubfoot patient adheres to the post-corrective bracing protocol to prevent relapse of the deformity that has turned the foot downward and elevated inwards. In order to encourage the patients’ compliance to the foot abduction orthosis (FAO), various designs have been introduced in the market in the hope of improving the rate of compliance. The purpose of this paper is to elucidate the assessment of the clubfoot patients’ FAO need at the orthopaedic clinic of Hospital Universiti Sains Malaysia in Kelantan, Malaysia. The assessment aims to understand the clubfoot patients’ lower limb movements, in order to generate ideas for the prototype design development to improve the FAO design based on the existing product in the market. The FAO that was referred for further design improvements are the Denis Browne splint and the Markel shoes. In addition, a total of 10 clubfoot patients’ parents were interviewed to obtain user experience data. This study suggests the need to eliminate the foot plates and the bulky protruding shoe and brace locks that are heavy due to the material use. Consequently, a conceptual design of the FAO was successfully developed as a proposal for potential future development of the working prototype to optimise the patients’ dynamic movement. Keywords - Clubfoot,Conceptual design, FAO design, Prototype development.